Art Theraphy Training in Increasing Self-Esteem in High School Students - hadi, Abdul Hadi; Aryani, Eka; Nurbaiti, Anifa Tuzzuhroh (PT FORMOSA CENDEKIA GLOBAL, 2024)
High school students' self-esteem problems can vary greatly and are influenced by many factors. Some common issues that can affect high school students' self-esteem include: social comparison, academic demands, and identity disorders and lack of social support. Responding to the problem of self-esteem, the service team provided an alternative solution with art therapy training to increase the self-esteem of high school students. The art therapy training process involved 40 high school students which included the process of drawing on aspects of the self including: strength, significance, ability and wisdom. The results of art therapy training using the paired T-test showed a figure of -6.17, mean -16.0, standard deviation 2.59, with a 2-tailed significance of 0.007. The results of the Paired Sample T-Test show that the T-value is -6.17 with a p-value of <0.001. The p-value is smaller than 0.05, which indicates that there is a significant difference in self-esteem abilities before and after participating in art therapy training. Apart from that, art therapy has an important role in adolescent mental health, especially in relation to individual self-esteem by overcoming social and emotional problems of adolescents after being given training.